Analysis of The Relationship of Children's Personality Development With Parenting Patterns of Parents Who Are Equally Working (Case Study of Children Aged 4-6 Years in Blok M Taman Cimanggu, Kedungwaringin Village, Tanah Sareal District, Bogor City) - Putra, Karantiano Sadasa; Fadhilah, Rumaisya Nur (Universitas Sebelas Maret, 2024)
The development of a child's personality is closely related to parental parenting issues. Parenting is an important thing that cannot be separated from a child's life to shape their personality and development to be perfect in their golden years. This research aims: To obtain data and information about the parenting patterns of parents who both work; To obtain data and information about the child's personality development; and to obtain information regarding whether or not there is a relationship between working parents' parenting styles and the child's personality development. The methodology used in the research is a survey method with a correlational approach. The research subjects consisted of 75 families as sample respondents taken randomly from the total research population of 92 families. The research was carried out in the Blok M area of Taman Cimanggu Housing, Kedungwaringin Village, Tanah Sareal District, Bogor City. The correlation coefficient value is ry = 0.631 at the significance level (α = 0.05), the strong relationship category. The research conclusion is that there is a strong and very significant positive relationship between the parenting style of parents who work together and the personality development of children aged 4-6 years.